An exploratory analysis of the tuberculosis control program of the states of bahia and goiás from a transaction cost theory perspective - Loureiro, Sebastião; Ferreira Júnior, Hamilton de Moura; Mota, Fábio Batista; Freitas, Lúcio Flávio da Silva (Saúde e Sociedade, 2013)
From a Transaction Cost Theory perspective, the paper aims to discuss the Programa de Controle da Tuberculose (PCT - Tuberculosis Control Program) of the States of Bahia and Goiás and their Capital Cities, Salvador and Goiânia. A case study was carried out applying a research questionnaire to the PCT managers. The results indicate: (a) low specificity in human assets; (b) low uncertainty - related to fluctuations in demand and to the introduction of new technologies (drugs); (c) aspects related to bounded rationality (incomplete information) are not important - related to the contract (PNCT) and the SINAN; (d) and high probability of opportunism (moral hazard), due to lack of monitoring of the actions, lack of punishment in case of default of actions agreed upon in the PNCT, and the current incentive regime.